Development and characterization of chronotherapeutic tablets of sacubitril-valsartan supramolecular complex using hupu gum and lannea gum by compression coating - Rajeswari Aleti, Kolapalli Venkata Ramana Murthy (Journal of Applied Pharmaceutical Science, 2023)
Sacubitril-valsartan supramolecular complex (SVSC), a first-in-class Angiotensin Receptor Neprilysin Inhibitor has been approved as a safe and effective treatment for Heart Failure with Reduced Ejection Fraction and reduces the risk of cardiovascular death and re-hospitalization in patients with striking rise in blood pressure during early morning hours. As cardiovascular events are well associated with circadian rhythms, chronotherapeutic drug delivery of SVSC at bedtime (around 10 p.m.) may be a potential approach. The aim and objective of the present investigation is to develop a chronotherapeutic drug delivery system of SVSC using natural gums by compression coating technique that is appropriate in achieving a predetermined lag time of 5-6 hours followed by maximum drug release within 1 hour to attain the required Cmax when the disease condition is at peak. Initially the core tablets were optimized which completely released the drug in 25 minutes. The optimized core tablets were subjected to compression coating with different ratios of hupu gum, lannea gum and channelling agent for the preparation of chronotherapeutic tablets. The optimized compression-coated tablets complied with the official and other requirements of tablets. Differential scanning calorimetry and Fourier-transformed infrared spectroscopy studies confirmed the drug and excipient compatibility. Among all formulations, Compression coated Tablets CCT3 met all the objectives of the present investigation and hence, was selected as an optimized compression-coated tablet suitable for chronotherapeutic drug delivery of SVSC in patients with heart failure.